Canola protein aerogels via salt-induced gelation and supercritical carbon dioxide drying. (5th April 2022) - FitzPatrick, Sarah E.; Deb-Choudhury, Santanu; Ranford, Steve; Staiger, Mark P.
Graphical abstract: Highlights: CaCl2 was used in a novel approach for Canola protein gelation. Supercritical CO2 drying was adapted to produce novel mesoporous Canola aerogels. BET specific surface area of a Canola aerogel and cryogel were compared. Abstract: Canola protein is used to produce novel, mesoporous, plant-based aerogels through a salt-induced gelation technique and supercritical carbon dioxide drying. The use of calcium chloride in formulation permits the preservation of gel monoliths during solvent exchange processing, customarily a major challenge in aerogel preparation. The gels could be successfully converted to aerogels by supercritical drying using accessible, off-the-shelf instrumentation, rather than the purpose-built systems commonly used in aerogel research. The use of calcium chloride represents a novel approach to canola protein gelation, achieving crosslinking via an environmentally-friendly approach. The first-ever supercritically-dried canola aerogels are shown to be mesoporous with an approximate density and specific surface area of 0.2 g/cm 3 and 113 m 2 /g, respectively. The typical low-densities (0.03 – 0.5 g/cm 3 ) and high surface areas (50 – 600 m 2 /g) of bioaerogels lend themselves to novel pharma- and nutraceutical applications, with canola aerogels now another addition to this family of advanced materials.